Method for improving air permeability of sintered ore bed

Through screening and grading mixing, uniform particulate materials are formed, and a special loose material rod and nine-roll fabric device are used during the sintering process, which solves the problem of reduced breathability of the sintered ore layer and improves the sintering efficiency and finished product quality.

CN119571052APending Publication Date: 2025-03-07TIANJIN IRON WORKS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411468560.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

During the thickening of the sintered ore layer, the reduction of air permeability leads to slowing down the sintering speed and overburning in some locations, increasing the carbon monoxide content, thereby increasing the difficulty and cost of environmentally friendly flue gas treatment.

Method used

Rebate ore and iron ore of different particle sizes were obtained through screening, and mixed in grades. A uniform particulate material was formed by long-term one-mix and two-mix. At the same time, multiple rows of round protrusions were arranged on the nine-roll fabric device to delay the fall of small-particle material, and combined with a special loose rod to improve the breathability of the material layer.

Benefits of technology

It significantly improves the breathability of the sintered ore layer, reduces the situation where small particles fill the gaps between large particles, improves sintering efficiency and finished product quality, and reduces environmentally friendly treatment costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571052A_ABST
    Figure CN119571052A_ABST
Patent Text Reader

Abstract

The invention relates to a method for improving the air permeability of a sintered ore bed, which comprises the steps of return ore screening, iron ore screening, particle mixing, conventional primary mixing, conventional secondary mixing, small-particle-size mixing, long-period primary mixing, long-period secondary mixing, sintering distribution, material loosening, sintering and the like. And in cooperation with the specific arrangement of grading material distribution and material loosening, the air permeability of the sintered ore layer is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sintering ore, and in particular to a method for improving the air permeability of a sintered ore material layer. Background Art

[0002] Sintering is an indispensable process in the modern steel industry. It is the main raw material for blast furnace ironmaking after sintering foreign ore and iron concentrate with fuel and flux. In order to reduce energy consumption and improve sintering efficiency, there is a growing trend towards thick layer sintering. However, as the layer thickens, the permeability of the sintered ore layer is affected. If the permeability is too low, the vertical sintering speed slows down, and some parts of the sintered ore are prone to overburning. Incomplete combustion will also increase the carbon monoxide content, further increasing the difficulty and cost of subsequent flue gas environmental protection treatment. If the permeability is not increased, it will directly lead to a decrease in the output and quality of sintered ore. Therefore, how to improve the permeability of the sintered ore layer has become an increasingly important research aspect.

[0003] At present, the air permeability is mainly improved through reasonable ore mixing, moderate increase of flux content, increase of upper layer temperature, graded material distribution, setting of material looseners, support base and graded material distribution.

[0004] Chinese invention patent publication CN112779415A discloses a device and method for improving the air permeability of sintering mixtures, which increases the air permeability by injecting steam and specifically setting the steam injection device to increase the temperature of the material layer, especially the top, but the effect needs to be improved.

[0005] The loosening rods in the prior art are generally set horizontally, and the shapes are mainly round rods or various groove-shaped horizontal parts. When laying the materials, the sintered ore buries the loosening rods. As the sintered ore after laying moves with the sintering trolley, the sintered ore gradually leaves the loosening rods. Since the sintered ore is granular, a certain horizontal void will still be retained at this position, thereby strengthening the distance between the materials, increasing the holes, and thus increasing the air permeability.

[0006] The existing graded material distribution is mainly carried out through a nine-roller distribution device. As the material moves downward in sequence on multiple rollers of the nine-roller distribution device, relatively large particles fall first and are thus distributed on the bottom layer, while smaller particles fall later due to slight obstructions of multiple rollers and are thus distributed on the top layer, thereby achieving graded material distribution. In order to strengthen the graded material distribution, the existing technology mainly sets the roller gap, angle and other aspects of the nine-roller distribution device to strengthen the graded material distribution.

[0007] Chinese invention patent publication CN118168334A discloses a nine-roller material distribution device and design method for a sintering process. By adjusting the distribution of the roll gaps, angles, etc. of the nine rolls, a segregation effect of material distribution (i.e., graded material distribution) is achieved, but its structure is relatively complex. Summary of the invention

[0008] The purpose of the present invention is to provide a thick layer sintering method.

[0009] The specific implementation is through the following technical solutions:

[0010] A method for improving the air permeability of a sintered ore layer comprises the following steps:

[0011] (1) Return ore screening: The sintered return ore is screened to obtain return ore with a particle size of less than 0.5 mm, return ore with a small particle size of 0.5-3 mm, return ore with a large particle size of 3-5 mm, return ore with an oversized particle size of 5-10 mm, and return ore with a base material size of more than 10 mm.

[0012] (2) Iron ore screening: The iron ore is screened to obtain fine iron ore with a particle size of less than 0.5 mm, small iron ore with a particle size of 0.5 to 3 mm, and large iron ore with a particle size of more than 3 mm.

[0013] (3) Particle mixing: The particle return ore obtained in step (1), the particle iron ore obtained in step (2) and the iron ore concentrate are mixed to obtain a particle mixture.

[0014] (4) Conventional one-step mixing: 80 to 90 parts by weight of the large-particle iron ore obtained in step (2), 5 to 15 parts by weight of the microparticle mixture obtained in step (3), 2.5 to 4.5 parts by weight of the fuel and 6 to 16 parts by weight of the flux are respectively placed in a mixer through a belt conveyor, 2 to 3 parts by weight of water are sprayed into the mixer, and the mixture is mixed once. The mixing time of the one-step mixing is 1 to 3 minutes.

[0015] (5) Conventional secondary mixing: the material obtained after the primary mixing in step (4) is placed in a granulator for secondary mixing and granulation, 3 to 6 parts by weight of water are sprayed into the secondary mixing and granulation process, and the secondary mixing and granulation time is 1 to 3 minutes to obtain a first mixed material.

[0016] (6) Small particle size mixing: The small particle size return ore of 0.5 to 3 mm obtained by screening in step (1) and the small particle size iron ore of 0.5 to 3 mm obtained by screening in step (2) are mixed to obtain a small particle size mixture.

[0017] (7) Long-cycle mixing: 75 to 85 parts by weight of the small-size iron ore obtained in step (6), 10 to 19 parts by weight of the microparticle mixture obtained in step (3), 3 to 5 parts by weight of the fuel and 5 to 15 parts by weight of the flux are respectively placed in a mixer through a belt conveyor, and 2.5 to 3.5 parts by weight of water are sprayed into the mixer for mixing. The mixing time is 4 to 8 minutes.

[0018] (8) Long-cycle secondary mixing: The material obtained after the primary mixing in step (7) is placed in a granulator for secondary mixing and granulation. During the secondary mixing and granulation process, 4 to 8 parts by weight of water are sprayed in. The secondary mixing and granulation time is 3 to 8 minutes to obtain a second mixed material.

[0019] Preferably, the method further comprises: (9) sintering material distribution: the return ore with a size larger than 10 mm obtained by screening in step (1) is laid on the sintering trolley as the base material, and the thickness of the base material is 33 to 55 mm; the super-sized return ore obtained in step (1) is laid on top of the base material, and the laying thickness is 10 to 20 mm; then, the first mixed material obtained in step (5) is laid on top of the super-sized return ore through a nine-roller spreading device, and the laying thickness is 50 to 60% of the total material layer thickness; then, the second mixed material obtained in step (8) is laid on the top through a nine-roller spreading device, and the laying thickness reaches the total material layer thickness.

[0020] (10) Loosening: A loosener is provided below the material distribution device. The loosener has a plurality of loosening rods which are horizontally placed conical structures with one end being thicker and the other end being thinner. The thicker end is connected to the side plate of the loosener base, and the thinner end is suspended in the air and faces the direction of movement of the sintering material on the sintering trolley. The cross-sectional diameter of the thin end 11 of the loosener rod is d, and the cross-sectional diameter of the thicker end of the loosener rod is D, wherein 0.21≤d / D≤0.46. During the sintering material distribution process, the loosener rod is horizontally placed above the base material. After the base material is distributed, the oversized return ore, the first mixed material and the second mixed material are distributed on the base material and the loosener rod is buried. As the sintering trolley continues to move the sintering material and distribute the material, a plurality of horizontal holes are continuously retained in the sintering material.

[0021] (11) Sintering: The material is laid out in the manner of step (9) and loosened in the manner of step (10). The sintering trolley continuously moves the sintering material and ignites the sintering at the same time. A high-temperature steam injection device consisting of a plurality of injection pipes is provided above the small ore trough of the sintering machine. The steam pressure is controlled to be 3.8 to 4.5 KPa to perform negative pressure sintering.

[0022] Preferably, the fuel is a mixture of 75-85wt.% coke powder and 15-25wt.% anthracite powder, and the average particle size of the mixture is less than 2mm, and the maximum particle size does not exceed 3.5mm.

[0023] Preferably, the flux is a mixture of 70-90 wt.% quicklime and 10-30 wt.% dolomite, and the particle size of the mixture is in the range of 1-3 mm.

[0024] Preferably, each roller of the nine-roller material distribution device is provided with multiple rows of round protrusions, the round protrusions are of a hemispherical structure, and the height of the round protrusions is 1.1-2.5 mm.

[0025] Preferably, the distance h between two adjacent rows of round protrusions on each roller of the nine-roller material distribution device is 3-5 mm, and the distance b between two adjacent round protrusions in each row is 3.5-4.6 mm.

[0026] Preferably, the roller gap between two adjacent rollers of the nine-roller material distribution device is 2-5 mm, and the angle between the plane formed by the nine rollers of the nine-roller material distribution device and the horizontal plane is 30-50°.

[0027] Preferably, the iron ore concentrate in step (3) accounts for 15 to 35 wt.% in the microparticle mixture.

[0028] Preferably, the angle α between the inclined surface of the loosening rod (i.e. the side of the horizontally placed frustum) and the vertical surface of the thick end of the loosening rod (i.e. the bottom surface of the horizontally placed frustum) is 85-89.5°.

[0029] Preferably, the loosening rod is connected to the side plate of the machine base through a thread. The thick end of the loosening rod is provided with a screw, the screw is provided with an external thread, the side plate of the machine base is provided with a through hole, the through hole is provided with an internal thread, and the external thread of the screw and the internal thread of the through hole are threadedly tightened and connected.

[0030] Preferably, a support base is arranged on the sintering trolley, the support base is arranged in multiple rows, and the top of each support base is arranged in an "M" shape (further preferably, the height of the support base is 25-38% of the height of the trolley guardrail).

[0031] Preferably, the iron ore is foreign ore such as Australian ore, Brazilian ore, South African ore, Russian ore, Ukrainian ore, Kazakhstan ore and / or Indian ore.

[0032] The technical effects of the present invention are:

[0033] (1) The existing ore blending mainly involves mixing the external ore and the iron ore concentrate once or twice to obtain a mixture with a main particle size of 4.5 to 5.5 mm. During the mixing process, the ore of about 3 mm and above is the core, and the iron ore concentrate and other ore powders with a particle size of less than 0.5 mm are adhesive powders. The adhesive powder adheres to the core layer by layer under the action of water and the mixture, thereby forming a mixture with a main particle size of 4.5 to 5.5 mm. However, the particles formed by the mixture are mixed at the same time, and particles within various particle size ranges exist. Although the particles will be graded and distributed through a nine-roller distribution device, the main particle size is large at the bottom and gradually decreases upwards. However, since particles of various particle sizes exist, small particles will naturally fill the gaps between large particles, thereby reducing or shrinking the gaps.

[0034] The present invention firstly performs conventional one-mixing and two-mixing of iron ore with large particle size of more than 3 mm in the raw materials and fine particle mixture, and at the same time, selects the iron ore with 1-3 mm in the raw materials separately and performs long-period one-mixing and two-mixing with the fine particle mixture selected separately for a relatively long time; thus, the main particle size of the mixture obtained by conventional one-mixing and two-mixing is relatively uniform between 5 and 5.5 mm (5-5.5 mm is more than 88%), and the overall particle size of the material obtained by long-period one-mixing and two-mixing is larger than that of the existing one-mixing and two-mixing due to the relatively long mixing. The particle size of this part of material obtained by mixing the second mixing is larger, basically 4.5-5.5mm, and the material with a particle size between 5 and 5.5mm accounts for about half of it. This makes the particle size of the material laid before sintering mainly concentrated between 5 and 5.5mm, that is, the main body is relatively uniform particles within this particle size range, and with the setting of graded cloth, the large particles are at the bottom and the relatively small particles are at the top, but the overall shape is relatively uniform, which greatly reduces the situation where too many small particles fill the gaps between large particles, thereby greatly improving the air permeability.

[0035] Moreover, in the existing sintering process, the heat accumulation during hot air negative pressure sintering will make the heat of the lower layer much higher than that of the upper layer, so that the heat is excessively uneven and affects the air permeability. Since the present invention performs a relatively long period of first and second mixing on the 1-3 mm iron ore material, the part of the iron ore material has relatively more particles adhering to the powder, fuel, etc. (the core is small, the outer layer will inevitably be thicker if the mixing time is extended), and this part of the material is arranged on the upper layer in accordance with the arrangement of the material distribution method of the present invention, so that the heat of the upper layer is increased during the sintering process, thereby further improving the heat distribution and further improving the air permeability.

[0036] (2) The loosening rods of the existing loosening devices, whether they are round rods or channel steel types, are modified in shape and are set horizontally. The two ends of the loosening rods are basically equal. In this way, when the sintering material moves with the sintering machine trolley, the material on the upper part of the loosening rod will instantly lose support and fall downward. Since the overall distribution has been completed and due to the presence of granular materials, the dynamic balance will be restored at this place to form a certain cavity. However, due to the instantaneous loss of support, the potential energy of a part of the granular material will be instantly converted into kinetic energy for downward movement, which makes the dynamic balance establishment time shorter, and the collision between the particles increases, resulting in the cavity. The diameter is too much smaller than the original diameter; at the same time, the sintering material moves with the sintering trolley and the material that has not completely left the loosening rod position causes the particles in this part to rotate due to friction with the loosening rod, thereby destroying the balance formed by the particles in the upper part of this place. The rotation causes vibration, which leads to further compaction between the particles in the upper part of this place (that is, the relatively small particles fill the gaps between the large particles). Although such a setting will form certain lateral voids, the diameter of the voids is reduced by a large proportion, and the upper part of this place is also compacted to a certain extent, which to a certain extent also has a certain negative impact on the air permeability of the upper part.

[0037] The present invention arranges the loosening rod to have a structure with one end larger than the other, and the smaller end moves toward the sintering machine trolley. As a result, when the material moves with the trolley, the material on the loosening rod moves as the diameter of the loosening rod gradually decreases, and the balance of the material changes gradually and slowly. Due to the contact between adjacent particles and the gradual decrease in diameter, the adjacent particles slowly support each other, and since the particle size of the mixed material formed in the batching process of the present invention is relatively uniform, the effect of this slow support is also enhanced (avoiding the poor stability of mutual support of particles that are too small due to large particle size differences and easy falling, resulting in poor stability of the cavity). The friction between the loosening rod and the gradually decreasing diameter is also reduced, and the upper material will not be vibrated and compacted too much due to friction, so that the cavity is formed relatively slowly. Since the formation of the cavity is relatively slow and gradual, the diameter of the cavity is not too different from the diameter of the end of the loosening rod. Therefore, the loosening effect of the loosening rod is greatly improved through this arrangement without causing negative impact on other parts.

[0038] (3) The existing nine-roller material distribution device has the function of strengthening the large material to be discharged first and the small material to be discharged later. The present invention separates the two initial particle size materials into different mixing methods so that the obtained material particle size is more uniform and the main part is a relatively large particle size. Therefore, the present invention sets multiple rows of round protrusions on the rollers of the nine-roller material distribution device in accordance with the characteristics of the material, and at the same time specifically limits the height, spacing, etc. of the round protrusions, so that it can delay the falling speed of the 4.5-5 mm part of the present invention and the material smaller than these particles. Due to the setting of the height, spacing, etc. of the round protrusions The impact on large-size materials is relatively small, and this part of the material will directly roll downward, while the relatively small-size materials will be blocked to a certain extent and their downward rolling speed will be slowed down. The setting of the round protrusions strengthens the blocking effect, and through the setting of height, spacing, etc., the blocking effect is targetedly strengthened for the specific small-size materials such as the present invention, so that the distinction between the falling timing of large-size and relatively small-size materials during distribution is further strengthened, so that the uniformity of the material particles in each layer is further strengthened, thereby further strengthening the air permeability of the sintered material layer.

[0039] 4. Since the reaction of calcium oxide and water to generate calcium hydroxide is an exothermic reaction, the present invention improves the material temperature to a certain extent by appropriately increasing the flux ratio and the ratio of quicklime in the flux, thereby further improving the air permeability of the sintered ore layer in conjunction with the setting of the particle size of the batching method. At the same time, since the material particle size set by the present invention is relatively average and uniform, the support effect between adjacent particles is enhanced compared to uneven particles, so an M-shaped support base is set to further enhance the air permeability. At the same time, since the present invention distributes the materials obtained by different raw materials and mixing methods in two batches, the particles are relatively uniform, so by reasonably setting the high-temperature steam pressure, the temperature of the upper material is enhanced to match the particle size, thereby further improving the air permeability of the sintered ore layer.

[0040] 5. The present invention only adds screening equipment and modifies the loosening rods and rollers. The equipment modification amount is relatively small, that is, the equipment modification cost is relatively low on the basis of ensuring the improvement of air permeability. The process only adds the screening process, thereby ensuring the cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 It is a structural schematic diagram of the front view of the loose material rod of the present invention.

[0042] Figure 2 It is a schematic diagram of the structure of each roller of the nine-roller material distribution device of the present invention.

[0043] Figure 3 It is a schematic structural diagram of the side view and the front view of the support base of the present invention.

[0044] Wherein: 11-the thin end of the loose material rod, 12-the thick end of the loose material rod, α-the angle between the inclined surface of the loose material rod and the vertical surface of the thick end of the loose material rod;

[0045] 20-roller of the nine-roller material distribution device, 21-round protrusion, h-distance between two adjacent rows of round protrusions, b-distance between two adjacent round protrusions in each row of round protrusions;

[0046] 30-Support base. DETAILED DESCRIPTION

[0047] The process technology scheme of the present invention is further described below by combining embodiments and drawings. Specific embodiments Unless otherwise described, each feature is only an example of a series of equivalent or similar features. It is only to help understand the present invention. Those skilled in the art should understand that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0048] Example 1

[0049] This embodiment is a method for improving the air permeability of a sintered ore layer carried out in a sintering workshop in Tianjin, comprising the following steps:

[0050] (1) Return ore screening: The sintered return ore is screened to obtain return ore with a particle size of less than 0.5 mm, return ore with a small particle size of 0.5-3 mm, return ore with a large particle size of 3-5 mm, return ore with an oversized particle size of 5-10 mm, and return ore with a base material size of more than 10 mm.

[0051] (2) Iron ore screening: The iron ore is screened to obtain fine iron ore with a particle size of less than 0.5 mm, small iron ore with a particle size of 0.5 to 3 mm, and large iron ore with a particle size of more than 3 mm.

[0052] (3) Particle mixing: The particle return ore obtained in step (1), the particle iron ore obtained in step (2) and the iron ore concentrate are mixed to obtain a particle mixture.

[0053] The iron concentrate accounts for 19 wt.% of the microparticle mixture. The ratio of microparticle return ore to microparticle iron ore is generally not limited and can be set according to the amount of return ore. In this embodiment, it is basically set to 1:2.

[0054] The iron ore in this embodiment is Australian ore.

[0055] (4) Conventional one-step mixing: 85 parts by weight of the large-size iron ore obtained in step (2), 8 parts by weight of the microparticle mixture obtained in step (3), 3.2 parts by weight of the fuel and 8 parts by weight of the flux are respectively placed in a mixer via a belt conveyor, 2.5 parts by weight of water are sprayed in, and one-step mixing is performed. The mixing time of one-step mixing is 2.5 minutes.

[0056] The fuel is a mixture of 80 wt.% coke powder and 20 wt.% anthracite powder, and the average particle size of the mixture is less than 2 mm, and the maximum particle size does not exceed 3.5 mm.

[0057] The flux is a mixture of 85wt.% quicklime and 15wt.% dolomite, and the particle size of the mixture is within the range of 1-3mm.

[0058] (5) Conventional secondary mixing: the material obtained after the primary mixing in step (4) is placed in a granulator for secondary mixing and granulation. During the secondary mixing and granulation process, 4.5 parts by weight of water is sprayed in. The secondary mixing and granulation time is 2 minutes to obtain a first mixed material.

[0059] (6) Small particle size mixing: The small particle size return ore of 0.5 to 3 mm obtained by screening in step (1) and the small particle size iron ore of 0.5 to 3 mm obtained by screening in step (2) are mixed to obtain a small particle size mixture.

[0060] (7) Long-cycle mixing: 80 parts by weight of the small-size iron ore obtained in step (6), 12 parts by weight of the microparticle mixture obtained in step (3), 3.5 parts by weight of the fuel and 10 parts by weight of the flux are respectively placed in a mixer through a belt conveyor, 3 parts by weight of water are sprayed in, and mixing is carried out. The mixing time is 5 minutes.

[0061] (8) Long-cycle secondary mixing: The material obtained after the primary mixing in step (7) is placed in a granulator for secondary mixing and granulation. During the secondary mixing and granulation process, 4.8 parts by weight of water is sprayed in. The secondary mixing and granulation time is 3.5 minutes to obtain a second mixed material.

[0062] (9) Sintering material distribution: The return ore with a size larger than 10 mm obtained by screening in step (1) is spread on the sintering trolley as the base material, and the thickness of the base material is 45 mm. The super-sized return ore obtained in step (1) is spread on the top of the base material, and the spread thickness is 15 mm. Then, the first mixed material obtained in step (5) is spread on the top of the super-sized return ore through a nine-roller spreading device, and the spread thickness is 55% of the total material layer thickness. Then, the second mixed material obtained in step (8) is spread on the top through a nine-roller spreading device, and spread to the total material layer thickness.

[0063] like Figure 2 As shown, each roller 20 of the nine-roller material distribution device is evenly provided with multiple rows of round protrusions 21, the round protrusions 21 are hemispherical structures, and the height of the round protrusions 21 is 2.1 mm. The distance h between two adjacent rows of round protrusions on each roller of the nine-roller material distribution device is 3.5 mm, and the distance b between two adjacent round protrusions in each row of round protrusions is 3.9 mm.

[0064] The roller gap between two adjacent rollers of the nine-roller material distribution device is 3..8mm, and the angle between the plane formed by the nine rollers of the nine-roller material distribution device and the horizontal plane is 39°.

[0065] And this embodiment Figure 3 As shown, a support base 31 is arranged on the sintering trolley. The support base 31 is arranged in multiple rows, and the top of each support base is set in an "M" shape. The height of the support base 31 in this embodiment is 33% of the height of the trolley guardrail.

[0066] (10) Loosening: A loosening device is provided below the material distributing device. The loosening device has multiple loosening rods such as Figure 1 The structure is shown as a horizontally placed truncated cone with one end thick and the other end thin, and the thick end is connected to the side plate of the base of the loosening device, and the thin end is suspended and faces the direction of movement of the sintering material of the sintering trolley. The diameter of the thin end 11 of the loosening rod in this embodiment is about 19 mm, and the diameter of the thick end 12 of the loosening rod is about 60.5 mm. The d / D of this embodiment is 0.314, which meets the requirement of 0.21≤d / D≤0.46. During the sintering distribution process, the loosening rod is horizontally placed above the base material. After the base material is laid, the super-sized return ore, the first mixed material and the second mixed material are laid on the base material and the loosening rod is buried. As the sintering trolley continues to move the sintering material and continues to distribute the material, multiple horizontal holes are continuously retained in the sintering distribution. The angle α between the inclined surface of the loosening rod in this embodiment and the vertical surface of the thick end 12 of the loosening rod is about 88°.

[0067] (11) Sintering: The material is laid out in the manner of step (9) and loosened in the manner of step (10). The sintering trolley continuously moves the sintering material and ignites the sintering at the same time. A high-temperature steam injection device consisting of a plurality of injection pipes is provided above the small ore trough of the sintering machine. The steam pressure is controlled to be 3.8 to 4.5 KPa to perform negative pressure sintering.

[0068] Example 2

[0069] This embodiment is a method for improving the air permeability of a sintered ore layer, which is also carried out in a sintering workshop in Tianjin, and includes the following steps:

[0070] (1) Return ore screening: The sintered return ore is screened to obtain return ore with a particle size of less than 0.5 mm, return ore with a small particle size of 0.5-3 mm, return ore with a large particle size of 3-5 mm, return ore with an oversized particle size of 5-10 mm, and return ore with a base material size of more than 10 mm.

[0071] (2) Iron ore screening: The iron ore is screened to obtain fine iron ore with a particle size of less than 0.5 mm, small iron ore with a particle size of 0.5 to 3 mm, and large iron ore with a particle size of more than 3 mm.

[0072] (3) Particle mixing: The particle return ore obtained in step (1), the particle iron ore obtained in step (2) and the iron ore concentrate are mixed to obtain a particle mixture.

[0073] The iron concentrate accounts for 21wt.% in the microparticle mixture. The ratio of microparticle return ore to microparticle iron ore is generally not limited and can be set according to the amount of return ore. In this embodiment, it is basically set to 1.5:2 (for example, it can be limited to 0.8-1.8:1.8-2.2 according to actual conditions).

[0074] The iron ore in this embodiment is also Australian ore.

[0075] (4) Conventional one-step mixing: 83 parts by weight of the large-size iron ore obtained in step (2), 6 parts by weight of the microparticle mixture obtained in step (3), 3.1 parts by weight of the fuel and 8.2 parts by weight of the flux are respectively placed in a mixer via a belt conveyor, 2.2 parts by weight of water are sprayed in, and one-step mixing is performed. The mixing time of one-step mixing is 2.8 minutes.

[0076] The fuel is a mixture of 82 wt.% coke powder and 18 wt.% anthracite powder, and the average particle size of the mixture is less than 2 mm, and the maximum particle size does not exceed 3.5 mm.

[0077] The flux is a mixture of 88 wt.% quicklime and 12 wt.% dolomite, and the particle size of the mixture is within the range of 1 to 3 mm.

[0078] (5) Conventional secondary mixing: the material obtained after the primary mixing in step (4) is placed in a granulator for secondary mixing and granulation. During the secondary mixing and granulation process, 4.8 parts by weight of water is sprayed in. The secondary mixing and granulation time is 2 minutes to obtain a first mixed material.

[0079] (6) Small particle size mixing: The small particle size return ore of 0.5 to 3 mm obtained by screening in step (1) and the small particle size iron ore of 0.5 to 3 mm obtained by screening in step (2) are mixed to obtain a small particle size mixture.

[0080] (7) Long-cycle mixing: 78 parts by weight of the small-size iron ore obtained in step (6), 12 parts by weight of the microparticle mixture obtained in step (3), 3.6 parts by weight of the fuel and 8 parts by weight of the flux are respectively placed in a mixer via a belt conveyor, 3.1 parts by weight of water are sprayed in, and mixing is performed. The mixing time is 4.5 minutes.

[0081] (8) Long-cycle secondary mixing: The material obtained after the primary mixing in step (7) is placed in a granulator for secondary mixing and granulation. During the secondary mixing and granulation process, 5 parts by weight of water is sprayed. The secondary mixing and granulation time is 4 minutes to obtain a second mixed material.

[0082] (9) Sintering material distribution: The return ore with a size larger than 10 mm obtained by screening in step (1) is spread on the sintering trolley as the base material, and the thickness of the base material is 42 mm. The super-sized return ore obtained in step (1) is spread on top of the base material, and the spread thickness is 16 mm. Then, the first mixed material obtained in step (5) is spread on top of the super-sized return ore through a nine-roller spreading device, and the spread thickness is 58% of the total material layer thickness. Then, the second mixed material obtained in step (8) is spread on the top through a nine-roller spreading device, and spread to the total material layer thickness.

[0083] like Figure 2 As shown, each roller of the nine-roller material distribution device is evenly provided with multiple rows of round protrusions 21, the round protrusions 21 are hemispherical structures, and the height of the round protrusions 21 is 1.8 mm. The distance h between two adjacent rows of round protrusions on each roller of the nine-roller material distribution device is 4.1 mm, and the distance b between two adjacent round protrusions in each row of round protrusions is 4 mm.

[0084] The roller gap between two adjacent rollers of the nine-roller material distribution device is 3.9 mm, and the angle between the plane formed by the nine rollers of the nine-roller material distribution device and the horizontal plane is 38°.

[0085] And this embodiment Figure 3 As shown, a support base 31 is arranged on the sintering trolley. The support base 31 is arranged in multiple rows, and the top of each support base is arranged in an "M" shape. The height of the support base in this embodiment is 29% of the height of the trolley guardrail.

[0086] (10) Loosening: A loosening device is provided below the material distributing device. The loosening device has two rows, each row has five loosening rods. Figure 1 The structure is shown as a horizontally placed truncated cone with one end thick and the other end thin, and the thick end is connected to the side plate of the base of the loosening rod, and the thin end is suspended and faces the direction of the sintering material moving on the sintering trolley. The cross-sectional diameter d of the thin end 11 of the loosening rod is 13mm, and the cross-sectional diameter D of the thick end 12 of the loosening rod is 58mm. In this embodiment, d / D=0.224, within the range of 0.21≤d / D≤0.46; during the sintering material distribution process, the loosening rod is horizontally placed above the base material, and after the base material is distributed, the super-sized return ore, the first mixed material and the second mixed material are distributed on the base material and the loosening rod is buried. As the sintering trolley continues to move the sintering material and continues to distribute the material, a plurality of horizontal holes are continuously retained in the sintering material. The overall length of the loosening rod in this embodiment is 2.3 meters.

[0087] The loosening rod of this embodiment is connected to the side plate of the machine base by threads, the thick end of the loosening rod is provided with a screw rod, the screw rod is provided with external threads, the side plate of the machine base is provided with a through hole, the through hole is provided with internal threads, and the external threads of the screw rod and the internal threads of the through hole are screwed and connected. With such a setting, when one of the loosening rods is broken, it only needs to be replaced by rotating the threads, and other loosening rods will not be affected.

[0088] (11) Sintering: The material is laid out in the manner of step (9) and loosened in the manner of step (10). The sintering trolley continuously moves the sintering material and ignites the sintering at the same time. A high-temperature steam injection device consisting of a plurality of injection pipes is provided above the small ore trough of the sintering machine. The steam pressure is controlled to be 3.8 to 4.5 KPa to perform negative pressure sintering.

[0089] Comparative Example 1

[0090] This comparative example is a method for improving the air permeability of a sintered ore layer, which is also carried out in a sintering workshop in Tianjin. The other settings are the same as those in Example 1, except that steps (1) to (3) and steps (6) to (8) are not carried out, that is, the original material is not screened for particle size, but the return ore other than the base material is directly mixed with the iron ore, fuel, flux, etc., and then the sintering operation is carried out. A loosening rod and a nine-roller feeding device with round protrusions are used. The results are shown in Table 1, which is a data comparison table of each embodiment and comparative example.

[0091] Comparative Example 2

[0092] This comparative example is a method for improving the air permeability of a sintered ore layer, which is also carried out in a sintering workshop in Tianjin. The other settings are the same as those in Example 1, except that the loosening rods in Example 1 are not used, but existing rod-shaped loosening rods with the same diameter are used, and the other settings are the same as those in Example 1. The results are shown in Table 1.

[0093] Comparative Example 3

[0094] This comparative example is a method for improving the air permeability of a sintered ore layer, which is also carried out in a sintering workshop in Tianjin. The other settings are the same as those in Example 1, except that an existing nine-roller material distribution device (i.e., no round protrusions are provided) is used, and the other settings are the same as those in Example 1. The results are shown in Table 1.

[0095] Table 1

[0096] <![CDATA[Sintering utilization coefficient (t / m 2 h)]]> Drum strength (%) Yield rate (%) Negative exhaust pressure (kPa) Example 1 1.358 80.86 79.21 -13.82 Comparative Example 1 1.201 80.41 77.56 -16.53 Comparative Example 2 1.225 80.51 77.63 -15.61 Comparative Example 3 1.213 80.58 77.52 -15.21

[0097] It can be seen from Table 1 that if the existing batching method (Comparative Example 1) is adopted, even if the loosening rod and the specific nine-roller feeding device are used, the negative pressure required for the exhaust is relatively large, so that the air permeability is much worse than that of Example 1. If the loosening rod uses the existing straight loosening rod (Comparative Example 2), even if the other settings are the same as those of Example 1, all indicators have a certain degree of decline, and the exhaust negative pressure is -15.61 kPa. Although it has been improved, the air permeability is still reduced compared with Example 1. If the existing nine-roller feeding device without round protrusions is used (Comparative Example 3), all indicators also decline to a certain extent, and the exhaust negative pressure is -15.21 kPa, that is, there are more small-particle materials than in Example 1 to fill the gaps between the large-particle materials, which causes the air permeability to decline relative to Example 1, resulting in a relatively slight decline in the yield rate and the drum strength as a whole. It can also be seen from Table 1 that although the orthogonal tests on multiple improved methods found that individual changes would have a downward trend on the air permeability relative to Example 1, the overall effect is better than that of the existing conventional method, and the effect of Example 1 is much better. Therefore, it is also proved that the various measures of the present invention are closely coordinated. The setting of the loosening rod is based on the uniform particle size of the material, and the size setting of the circular protrusions on the rollers of the nine-roller feeding device is also coordinated with the particle size distribution obtained after the specific second mixing of the present invention. Therefore, the various measures of the present invention are closely coordinated.

Claims

1. A method for improving the air permeability of a sintered ore layer, characterized in that: The steps include: (1) Screening of returned ore: Screening of sintered returned ore to obtain returned ore with particle size less than 0.5 mm, returned ore with small particle size of 0.5-3 mm, returned ore with large particle size of 3-5 mm, returned ore with super particle size of 5-10 mm, and returned ore with base material larger than 10 mm; (2) Iron ore screening: Screening the iron ore to obtain fine iron ore with a particle size of less than 0.5 mm, small iron ore with a particle size of 0.5 to 3 mm, and large iron ore with a particle size of more than 3 mm; (3) Particle mixing: mixing the particle return ore obtained in step (1), the particle iron ore obtained in step (2) and the iron ore concentrate to obtain a particle mixture; (4) Conventional one-step mixing: 80-90 parts by weight of the large-size iron ore obtained in step (2), 5-15 parts by weight of the microparticle mixture obtained in step (3), 2.5-4.5 parts by weight of the fuel and 6-16 parts by weight of the flux are respectively placed in a mixer through a belt conveyor, 2-3 parts by weight of water are sprayed in, and one-step mixing is performed. The mixing time of one-step mixing is 1-3 minutes. (5) Conventional secondary mixing: placing the material obtained after the primary mixing in step (4) into a granulator for secondary mixing and granulation, spraying 3 to 6 parts by weight of water during the secondary mixing and granulation process, and the secondary mixing and granulation time is 1 to 3 minutes to obtain a first mixed material; (6) Small particle size mixing: mixing the small particle size return ore of 0.5 to 3 mm obtained by screening in step (1) and the small particle size iron ore of 0.5 to 3 mm obtained by screening in step (2) to obtain a small particle size mixture; (7) long-cycle mixing: 75 to 85 parts by weight of the large-size iron ore obtained in step (6), 10 to 19 parts by weight of the microparticle mixture obtained in step (3), 3 to 5 parts by weight of the fuel and 5 to 15 parts by weight of the flux are respectively placed in a mixer through a belt conveyor, 2.5 to 3.5 parts by weight of water are sprayed in, and the mixture is mixed once. The mixing time is 4 to 8 minutes. (8) Long-cycle secondary mixing: The material obtained after the primary mixing in step (7) is placed in a granulator for secondary mixing and granulation. During the secondary mixing and granulation process, 4 to 8 parts by weight of water are sprayed in. The secondary mixing and granulation time is 3 to 8 minutes to obtain a second mixed material.

2. The method for improving the air permeability of a sintered ore layer according to claim 1, characterized in that: After step (8), the method further includes the following steps: (9) Sintering material distribution: the sieving return ore with a size larger than 10 mm obtained in step (1) is laid on the sintering trolley as the base material, and the thickness of the base material is 33 to 55 mm. The super-sized return ore obtained in step (1) is laid on the top of the base material, and the laying thickness is 10 to 20 mm. Then, the first mixed material obtained in step (5) is laid on the top of the super-sized return ore through a nine-roller distribution device, and the laying thickness is 50 to 60% of the total material layer thickness. Then, the second mixed material obtained in step (8) is laid on the top through a nine-roller distribution device, and the laying thickness reaches the total material layer thickness. (10) Loosening: A loosening device is provided below the material distribution device. The loosening rods of the loosening device are horizontally placed truncated cone structures with one end thicker and the other end thinner. The thick end is connected to the side plate of the loosening device base, and the thin end is suspended in the air and faces the direction of movement of the sintering material on the sintering trolley. The cross-sectional diameter of the thin end of the loosening rod is d, and the cross-sectional diameter of the thick end of the loosening rod is D, wherein 0.21≤d / D≤0.46; during the sintering material distribution process, the loosening rod is horizontally placed above the base material. After the base material is laid, the oversized return ore, the first mixed material and the second mixed material are laid on the base material and the loosening rod is buried. As the sintering trolley continues to move the sintering material and continue to distribute the material, a plurality of horizontal holes are continuously retained in the sintering material distribution; (11) Sintering: The material is laid out in the manner of step (9) and loosened in the manner of step (10). The sintering trolley continuously moves the sintering material and ignites the sintering at the same time. A high-temperature steam injection device consisting of a plurality of injection pipes is provided above the small ore trough of the sintering machine. The steam pressure is controlled to be 3.8 to 4.5 KPa to perform negative pressure sintering.

3. The method for improving the air permeability of a sintered ore layer according to claim 2, characterized in that: The fuel is a mixture of 75-85wt.% coke powder and 15-25wt.% anthracite powder, and the average particle size of the mixture is less than 2mm, and the maximum particle size does not exceed 3.5mm.

4. The method for improving the air permeability of a sintered ore layer according to claim 2, characterized in that: The flux is a mixture of 70-90wt.% quicklime and 10-30wt.% dolomite, and the particle size of the mixture is within the range of 1-3mm.

5. The method for improving the air permeability of a sintered ore layer according to claim 2, characterized in that: Each roller of the nine-roller material distribution device is provided with multiple rows of round protrusions, each of which is a hemispherical structure and has a height of 1.1 to 2.5 mm; The distance h between two adjacent rows of round protrusions on each roller of the nine-roller material distribution device is 3-5 mm, and the distance b between two adjacent round protrusions in each row of round protrusions is 3.5-4.6 mm.

6. The method for improving the air permeability of a sintered ore layer according to claim 4 or 5, characterized in that: The roller gap between two adjacent rollers of the nine-roller material distribution device is 2-5 mm, and the angle between the plane formed by the nine rollers of the nine-roller material distribution device and the horizontal plane is 30-50°.

7. The method for improving the air permeability of a sintered material layer according to claim 2, characterized in that: The iron ore concentrate in step (3) accounts for 15-35 wt.% in the microparticle mixture.

8. The method for improving the air permeability of a sintered ore layer according to claim 2, characterized in that: The angle α between the inclined surface of the loose material rod and the vertical surface of the thick end of the loose material rod is 85-89.5°.

9. The method for improving the air permeability of a sintered ore layer according to claim 2 or 5, characterized in that: A support base is arranged on the sintering trolley, and the support base is arranged in multiple rows, and the top of each support base is arranged in an "M" shape.

10. The method for improving the air permeability of a sintered material layer according to claim 2, characterized in that: The iron ore is foreign ore from Australia, Brazil, South Africa, Russia, Ukraine, Kazakhstan and / or India.

Citation Information

Patent Citations

  • Device and method for improving air permeability of sintering mixture

    CN112779415A

  • Nine-roller material distribution device for sintering process and design method

    CN118168334A